Gardner syndrome with unusual maxillofacial manifestation - Oliveira, Marina Reis [UNESP]; Rodrigues, Willian Caetano [UNESP]; Gabrielli, Mario Francisco Real [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Onofre, Mirian Aparecida [UNESP]; Filho, Valfrido Antonio Pereira [UNESP] (Wolters Kluwer, 2016)
Gardner syndrome is a rare autosomal-dominant condition characterized by the presence of intestinal polyposis, multiple osteomas, and tumors of the hard and soft tissues. This paper describes a patient of Gardner syndrome with unusual maxillofacial manifestation with presence of fibromyxomatous injury in jaw, coronoid hyperplasia, and multiple osteomas diffusely distributed in the craniomaxillofacial skeleton. Imaging examinations have identified craniofacial manifestations and the patient was referred to the gastroenterologist who confirmed the diagnosis of Gardner syndrome. The early diagnosis of this syndrome is important since intestinal polyps have high potential for malignant transformation. It is therefore essential that dentists are familiar with the maxillofacial features of this condition, since they precede the intestinal polyposis and encourage early diagnosis. In addition to classic maxillofacial signs of this syndrome, one must consider that, although it is rare, other injuries may be present such as those described in this clinical patient.
Keywords: Coronoid process hypertrophy; fibromixoma; Gardner syndrome; impacted teeth; intestinal polyposis; osteoma